Transfer Printed Microcell Array for Stretchable Organic Solar Cells. (4th September 2015) - Kang, Nami; Choi, Wonjung; Kim, Hogyoung; Kim, Chang Su; Jo, Sungjin
Abstract : We have successfully demonstrated the proof-of-concept for stretchable organic photovoltaics (OPVs) using a transfer-printed microcell array, which represents the first stretchable OPVs using conventional device layouts that employ indium tin oxide (ITO) electrodes. Upon releasing the pre-strain, the interconnects adopt non-coplanar serpentine shapes because of the compressive forces and the absence of chemical bonds between the interconnects and the substrate. The microcell array can withstand mechanical deformation because the serpentine shape interconnects accommodate most of the applied strain. These results may provide practical routes for the fabrication of stretchable OPVs for use in various soft electronic applications.